Imaginary of the professional future in a pandemic: Reflection Fromm Social Communication - Sochimilca-Socha, Orlando Arturo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The reflection on the professional practices of the students of Social Communication of the Cooperative University of Colombia is in the environment of the confinement forced by the pandemic caused by COVID 19, during 2020 and 2021. The analysis of imaginaries about its development was carried out from the university, organizational and student perspective; for which an evaluation was carried out with those responsible in the organizations and the final reports of the students, to conclude that there are positive, negative and to improve aspects in relation to the Critical Model with Competency Approach.